2015
DOI: 10.1111/1758-2229.12257
|View full text |Cite
|
Sign up to set email alerts
|

First report of a multidrug‐resistant Klebsiella pneumoniae of sequence type 11 causing sepsis in a free‐ranging beaver (Castor fiber)

Abstract: Klebsiella pneumoniae of sequence type (ST) 11 is a hyper-epidemic nosocomial clone spreading worldwide among humans and also emerging in pets. In this report, we describe a clinical case of fatal sepsis due to this multidrug-resistant (MDR) pathogen in a Eurasian beaver. The isolate showed resistance to six different classes of antimicrobials including third generation cephalosporins and fluoroquinolones. This is the first report describing the detection of a MDR K. pneumoniae ST11 in a free-ranging animal. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Loncaric et al (2016) found an SHV-11-encoding K. pneumoniae strain from mouflon ( Ovis orientalis musimon ) in Austria belonging to the epidemic clone ST11, which is associated with carbapenemase (Hu et al, 2016; Kim et al, 2013; Lee et al, 2016; Voulgari et al, 2016) and ESBL in humans worldwide (Hu et al, 2016; Lee et al, 2011b; Lu et al, 2016; Sennati et al, 2012), and previously described in companion animals and Eurasian beaver ( Castor fiber ) (Donati et al, 2014; Pilo et al, 2015). In Algeria, all 17 bla CTX-M-15 -bearing K. pneumoniae isolates found in wild boars and Barbary macaques belong to ST584, which has also been detected in silver gulls as carriers of carbapenemase IMP-4 in Australia (Dolejska et al, 2016) as well as in human in Brazil ().…”
Section: Esbl-producing Enterobacteriaceae From Wildlifementioning
confidence: 88%
See 1 more Smart Citation
“…Loncaric et al (2016) found an SHV-11-encoding K. pneumoniae strain from mouflon ( Ovis orientalis musimon ) in Austria belonging to the epidemic clone ST11, which is associated with carbapenemase (Hu et al, 2016; Kim et al, 2013; Lee et al, 2016; Voulgari et al, 2016) and ESBL in humans worldwide (Hu et al, 2016; Lee et al, 2011b; Lu et al, 2016; Sennati et al, 2012), and previously described in companion animals and Eurasian beaver ( Castor fiber ) (Donati et al, 2014; Pilo et al, 2015). In Algeria, all 17 bla CTX-M-15 -bearing K. pneumoniae isolates found in wild boars and Barbary macaques belong to ST584, which has also been detected in silver gulls as carriers of carbapenemase IMP-4 in Australia (Dolejska et al, 2016) as well as in human in Brazil ().…”
Section: Esbl-producing Enterobacteriaceae From Wildlifementioning
confidence: 88%
“…In addition to CMY-2, DHA-type AmpC β-lactamase genes have also been detected in K. pneumoniae from mouflons ( Ovis orientalis musimon ) in Austria, E. coli from hill mynah ( Gracula religiosa ) in Saudi Arabia, and K. pneumoniae ST11 isolates from Eurasian beaver ( Castor fiber ) in Switzerland (Hassan & Shobrak, 2015; Loncaric et al, 2016; Pilo et al, 2015). FOX-5 encoded by an IncA/C plasmid has been obtained from K. pneumoniae isolates in the US (Poirel et al, 2012).…”
Section: Plasmid-mediated Ampc β-Lactamase-producing Enterobacteriacementioning
confidence: 99%
“…To the best of our knowledge, there is only one report regarding the association of K . pneumoniae ST11 carrying bla genes with wildlife [ 31 ]. In contrast to the studies dealing with the presence of bla genes and PMQR in E .…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, bla DHA-1 is detected mostly in Klebsiella pneumoniae and E. coli, and it is harbored by plasmids of different sizes and incompatibility groups (8,29). In Switzerland, bla DHA-1 has been associated with plasmids R, FIIk, F, and HIB (30)(31)(32). To our knowledge, only two IncFII plasmids carrying bla DHA-1 were previously reported: one (82 kb) in E. coli from the United Kingdom (GenBank accession no.…”
mentioning
confidence: 99%